A STUDY ON THE EFFECT OF SOCIAL CAPITAL ON THE PERFORMANCE OF SELF HELP GROUP WOMEN MICRO ENTREPRENEURS IN KERALA - BABU. P AND A K SARADA (International Journal of Research in Social Sciences, 2014)
Official poverty eradication programmes in India has been primarily centered on the promotion of women self help groups (SHG) since 1990s. Most women who became micro entrepreneurs under the SHG movement lack basic entrepreneurial skills necessary to play their entrepreneurial role effectively. Such forced entrepreneurship actually resulted only in increased indebtedness to a large number of women. Social capital has been projected as a key resource in entrepreneurial success. In this context the study provides empirical evidence to the relevance of social capital in micro business success on the basis study made among SHG women micro entrepreneurs in Kerala